Perawatan yang Beracun: Kerja Perawatan Perkebunan dan Reproduksi Sosial dalam Perkebunan Monokultur Sawit - Sinaga, Hariati (Yayasan Jurnal Perempuan, 2023)
The expansion of oil palm plantation has drawn scholarship attention. On one hand, studies have examined how oil palm plantation development serves an important instrument for employment creation, poverty alleviation and rural development. On the other, there is plenty of research that shows adverse impacts of such expansion on socio-ecological conditions. This includes the recruitment of women plantation workers into maintenance work with flexible labour relations. Meanwhile, literature on oil palm plantations in Indonesia has not paid significant attention on care work. Employing feminist political economy perspective, this article attempts to understand care work in monoculture oil palm plantations, particularly in relations to maintenance work on plantation. Through the concept of social reproduction, care work is understood in a broader terms as a way to draw the entanglement between production and reproduction in monoculture oil palm plantations. This article argues that women workers participation into maintenance work on plantations show the articulation of social relations based on patriarchal system with palm oil competition in the global market. From the perspective of the women workers, participation in the maintenance work is viewed as a livelihood strategy. The strategy that involves works with risk of regular exposure to toxic chemicals is understood as toxic care.